2016
DOI: 10.1002/anie.201601562
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dirhenadehydro[12]annulenes

Abstract: The 12-membered-ring metallacycles [mer-Re{≡CCH=C(R)C≡C-}Cl(PMe2 Ph)3 )]2 (R=CMe3 , 1-adamantyl), which are organometallic analogues of antiaromatic octadehydro[12]annulene, are prepared by heating the methyl carbyne complexes mer-Re{≡CCH=C(R)C≡CH}(CH3 )Cl(PMe2 Ph)3 . An intermolecular σ-bond metathesis between the Re-CH3 bond and the acetylenic C-H bond is proposed for their formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…The identities of complexes 14 have been confirmed by X‐ray diffraction studies and are supported by their spectroscopic data. We have reported in our preliminary report that the solid‐state structure of 14 a contains an essentially planar twelve‐membered metallacycle. We now found that the complex 14 b has structural features like those of 14 a , as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The identities of complexes 14 have been confirmed by X‐ray diffraction studies and are supported by their spectroscopic data. We have reported in our preliminary report that the solid‐state structure of 14 a contains an essentially planar twelve‐membered metallacycle. We now found that the complex 14 b has structural features like those of 14 a , as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…In our preliminary communication, we reported that the methyl rhenium carbynes 13 containing a terminal alkynyl group can eliminate methane to give the dirhenadehydro[12]annulenes 14 via a σ‐bond metathesis mechanism (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported metallacycles includem etallabenzenes, [1,2] metallabenzynes, [3,4] metallaannulenes, [5] and other metallacycles. Reported metallacycles includem etallabenzenes, [1,2] metallabenzynes, [3,4] metallaannulenes, [5] and other metallacycles.…”
Section: Introductionmentioning
confidence: 99%